2022
DOI: 10.3390/cells11244085
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Humanized Versus Murinized CD19 and CD22 CAR T-Cell Cocktail Therapy for Refractory/Relapsed B-Cell Lymphoma

Abstract: CD19 chimeric antigen receptor T-cell (CAR-T) therapy is efficacious for refractory/relapsed (R/R) B-cell hematological malignancies, yet relapse due to CD19 antigen escape remains a challenge. Our trial explored simultaneous targeting of multiple B-cell antigens as a therapeutic approach that may reduce the risk of relapse. We tested the safety and efficacy of CAR19/22 T-cell cocktail therapy including murinized and humanized products among patients with R/R aggressive B-cell lymphoma. In the group that recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…The immunogenicity and targeted toxicity of CAR structures remains an important consideration in the development of treatments using this approach [ 59 ]. The immunogenicity of CAR T cells can trigger an immune response against CAR, leading to rejection, deletion, and clearance of CAR T cells, which is also a crucial factor affecting the long-term persistence of CAR T cells in the body [ 60 ]. Previous studies have indicated that the upregulation of CD28 or 4-1BB signals in CAR structures, as well as high expression of CAR molecules in T cells, result in increased cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…The immunogenicity and targeted toxicity of CAR structures remains an important consideration in the development of treatments using this approach [ 59 ]. The immunogenicity of CAR T cells can trigger an immune response against CAR, leading to rejection, deletion, and clearance of CAR T cells, which is also a crucial factor affecting the long-term persistence of CAR T cells in the body [ 60 ]. Previous studies have indicated that the upregulation of CD28 or 4-1BB signals in CAR structures, as well as high expression of CAR molecules in T cells, result in increased cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Also PFS was more favorable in the humanized CAR-T cell therapy. Interestingly, CAR19 or CAR22 T-cells were still detected in the peripheral blood, cerebrospinal fluid and hydrothorax months to one year later after receiving humanized CAR T-cells, which may have the potential to mediate long-term disease remission [53].…”
Section: Cd19/cd22mentioning
confidence: 99%